Athen's game of chicken or the conditional dependence between the Greek banks. (2016) - Derbali, Abdelkader; Hallara, Slaheddine; Sy, Aida
In this paper, we investigate empirically evidence to examine the conditional dependence between the Grecian banks. Then, we use, first, the methodology GARCH-DCC based on the dynamic process of dependence and, second, we use the methodology GARCH-DECO based on the constant process of dependence. The two methodologies DCC and DECO proposed, respectively, by Engle (2002), and Engle and Kelly (2009) are improved from a sample composed by 18 Grecian banks listed in the Athens Exchange over the period 2nd January 2006 from 31st December 2012. The results show the effect of time varying variance and dynamic correlations on the assets returns of all banks listed in the stock market of Greece. These results show that asset returns of banks are highly correlated positively, especially, after the outbreak of the financial crisis of 2007.